The Politics of Law in the Madrid Protocol Ratification in the Form of President Regulation Related to Trademark Registration - Tiopan, Demson; Kurniawan, Shelly (Technium Social Sciences Journal, 2020)
The implementation of Madrid System in Indonesia since the 1st January in 2018 is expected to have a positive impact in terms of international trademark registration to allow and protect entrepreneurial entities, from individual, legal, and business entities to compete globally.On the other hand, trademark registration originated from Indonesia using the Madrid Protocol Systemto other countries is still considerably minimal compared to trademark registration from other countries to Indonesia. There are issues point out in this writing, specifically to describe the politics of law in the ratification of Protocol related to the Madrid Agreement Concerning the International Trademark Registration, 1989 and also obstacle adhere after the ratification of the Madrid Protocol in the registration of international trademarks in Indonesia. Result of this study is that the ratification of Protocol related to the Madrid Agreement regarding International Trademark Registration, 1989 conducted by Indonesian government through Republic of Indonesia Presidential Regulation No. 92 in 2017 regarding ratification of Protocol Related to the Madrid Agreement Regarding International Trademark Registration, 1989 contained in State Gazette No.212 in 2017 is already appropriate. However, judging from the timeframe of the Madrid Protocol’s formation was formed already since1989, the ratification in Indonesia is considered delayed, knowing that this ratification is very beneficial for protecting entrepreneurs to expand their business abroad. Obstacles revolve around the implementation of the Madrid Protocol system in Indonesia are due to several reasons; few of them are of lack of encouragement from the entrepreneurial entities to register their brand, thougherapplication conditions from some countries compared to in Indonesia, and unavailability of online platform to register international trademark.